Lopesiodinia alvarengai Prado, 1973 (Odiniidae: Traginopinae) with the first description of the male and the neotype designation - Tôrres, Alice; Rafael, José A.; Gaimari, Stephen D.; Limeira-De-Oliveira, Francisco (Zootaxa, 2024)
The type specimen of Lopesiodinia alvarengai Prado is lost. It is being redescribed and illustrated based on specimens from the type locality (Jacareacanga, Pará, Brazil) and the neotype is here designated with the purpose of clarifying the taxonomic status and objectively securing stability of nomenclature.